Weed suppression by cover crops: comparative on‐farm experiments under integrated and organic conservation tillage. (31st August 2015) - Dorn, B; Jossi, W; van der Heijden, M G A
Summary: Cover crops are increasingly being used for weed suppression and to enhance the sustainability of agro‐ecosystems. However, the suitability of cover crops for weed suppression in integrated and organic conservation tillage systems is still poorly investigated. Therefore, a 2‐year field study at eight sites was conducted to test the weed suppressive potential of six legume‐based cover crops, with the aim to reduce herbicide input or mechanical weed management interventions. In all experiments, cover crops were directly sown after cereals before next year's main crop (grain maize or sunflower). The presence of cover crops caused a 96% to 100% reduction of weed dry matter at the four sites managed under integrated production, while effects were lower at the four sited managed under organic production, ranging from 19% to 87%. Cover crops that covered soil quickly and which produced much dry matter had the best weed suppressive potential. However, their weed suppressing effect was difficult to predict, as it depended on the year of the investigation, experimental site, cover crop species, the speed of soil cover in autumn and the density of the resulting mulch layer in spring. The study demonstrated that cover crops are a useful tool to suppress weeds under integrated and organic conservation tillage practices. Our recommendation for supporting weed management in conservation tillage systems is to use locally adapted cover crops that have rapid establishment, good soil coverage and high dry matter production. However, additional weed management measures are required for reliable weed control under on‐farm conditions.